The Malvastrum Yellow Vein Virus C4 Protein Promotes Disease Symptom Development and Enhances Virus Accumulation in Plants - Jing, Chenchen; Li, Pengbai; Zhang, Jiayuan; Wang, Rui; Wu, Gentu; Li, Mingjun; Xie, Li; Qing, Ling (Frontiers in Microbiology, 2019)
The begomovirus C4 protein is required for disease symptom development during virus infection in host plants. It can reprogram the cell cycle process for more efficient virus accumulation. In this study, we showed that the Malvastrum yellow vein virus (MaYVV) C4 protein could cause leaf upward curling and flower malformation, and increase virus accumulation in plants using PVX-based transient expression technology. We also demonstrated that, in the presence of its cognate betasatellite DNA (MaYVB), a mutant MaYVV, defective in producing the C4 protein (MaYVVΔC4), caused a delayed and alleviated infection in Nicotiana benthamiana. The MaYVV C4 transgenic plants showed leaf upward curling and uneven leaf lamina growth. Microscopic analysis showed that the epidermal cells of the C4 transgenic leaves were much smaller than those in the wild type (WT) leaves, and the mesophyll cells arrangement of transgenic plants was significantly altered. Inoculation of C4 transgenic plants with MaYVVΔC4 alone or associated with MaYVB showed that the transgenic C4 protein could rescue the accumulation of this mutant virus. Other transient expression assays also confirmed that the MaYVV C4 protein could suppress silencing of a GFP gene. In summary, our results indicate that the MaYVV C4 protein is a determinant of disease symptom and viral DNA accumulation. This protein can also function as a suppressor of RNA silencing and alter cell division and expansion.